2019
DOI: 10.1074/jbc.rev119.007060
|View full text |Cite
|
Sign up to set email alerts
|

Regulator of G-protein signaling (RGS) proteins as drug targets: Progress and future potentials

Abstract: Edited by Henrik G. Dohlman G protein-coupled receptors (GPCRs) play critical roles in regulating processes such as cellular homeostasis, responses to stimuli, and cell signaling. Accordingly, GPCRs have long served as extraordinarily successful drug targets. It is therefore not surprising that the discovery in the mid-1990s of a family of proteins that regulate processes downstream of GPCRs generated great excitement in the field. This finding enhanced the understanding of these critical signaling pathways an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
95
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 101 publications
(95 citation statements)
references
References 157 publications
(191 reference statements)
0
95
0
Order By: Relevance
“…Though the role of these RGS proteins in PD has clearly been established through genetic animal models, at present, they cannot be tested pharmacologically. Indeed, currently identified RGS protein inhibitors are not selective (Hayes et al, 2018, O'Brien et al, 2019. In addition, these inhibitors lack required tissue and neuronal specificity and likely will affect multiple tissues where these RGS proteins are expressed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the role of these RGS proteins in PD has clearly been established through genetic animal models, at present, they cannot be tested pharmacologically. Indeed, currently identified RGS protein inhibitors are not selective (Hayes et al, 2018, O'Brien et al, 2019. In addition, these inhibitors lack required tissue and neuronal specificity and likely will affect multiple tissues where these RGS proteins are expressed.…”
Section: Resultsmentioning
confidence: 99%
“…While these pharmacological therapies successfully inhibit GPCR signaling, they often lack tissue specificity. Similarly, the search for selective RGS inhibitors and/or activators has proven difficult (Hayes et al, 2018, Neubig and Siderovski, 2002, O'Brien et al, 2019. In evidence of this, Hayes et al (2018) recently demonstrated that each of 13 identified RGS4 inhibitors inhibited other members of the RGS protein family, sometimes with equal or greater potency than for RGS4.…”
Section: Resultsmentioning
confidence: 99%
“…90 Furthermore, the regulator of G protein-signaling (RGS) proteins constitute an important intracellular component in the control of GPCR signaling. 91 For example, RGS proteins have been implicated in the interaction of CB 1 receptor with dopamine D 2 receptor regarding the regulation of eCB-mediated retrograde synaptic signaling of striatal neurons. 92 Altogether, these observations suggest that CB 1 receptor signaling can depend on the availability of the intracellular G protein pool and on the specific ligand that activates the CB 1 receptor.…”
Section: Neurobiology Of Cannabinoid Receptor Signaling -Lutzmentioning
confidence: 99%
“…GTP hydrolysis by the inherent GTPase activity, which is often supported by GTPase-activating proteins (GAPs), then terminates G signaling and allows G␣ GDP to associate with G␤␥ to return the G protein to the inactive state ( Fig. 2) (1,(46)(47)(48). This activation-inactivation cycle suffices to explain why guanine nucleotide dissociation inhibitors (GDIs), such as FR and YM, are efficient terminators of G protein signaling; they block the rate-limiting step of the cycle, which is GDP release (Fig.…”
Section: The Delicate Balance Between On and Off Statesmentioning
confidence: 99%
“…Unlike the conventional GPCR-targeted therapies that intervene with categories (i) and (ii), the therapeutic concept discussed in this review is also, and perhaps especially, effective for category (iii). GAPs, category (iv), are not within the scope of this review and interested readers may refer to several excellent reviews on this topic elsewhere (46,47,(54)(55)(56).…”
Section: The Delicate Balance Between On and Off Statesmentioning
confidence: 99%